Advances in the knowledge of amphizoic amoebae infecting fish - Dyková, Iva; Lom, Jiří (Folia Parasitologica)
Free-living amoebae infecting freshwater and marine fish include those described thus far as agents of fish diseases, associated with other disease conditions and isolated from organs of asymptomatic fish. This survey is based on information from the literature as well as on our own data on strains isolated from freshwater and marine fish. Evidence is provided for diverse fish-infecting amphizoic amoebae. Recent progress in the understanding of the biology of Neoparamoeba spp., agents responsible for significant direct losses in Atlantic salmon and turbot industry, is presented. Specific requirements of diagnostic procedures detecting amoebic infections in fish and taxonomic criteria available for generic and species determination of amphizoic amoebae are analysed. The limits of morphological and non-morphological approaches in species determination are exemplified by Neoparamoeba, Vannella and Platyamoeba spp., which are the most common amoebae isolated from fish gills, Acanthamoeba and Naegleria spp. isolated from various organs of freshwater fish, and by other unique fish isolates of the genera Nuclearia, Thecamoeba and Filamoeba. Advances in molecular characterisation of SSU rRNA genes and phylogenetic analyses based on their sequences are summarised. Attention is particularly given to specific diagnostic tools for fish-infecting amphizoic amoebae and ways for their further development.